Análisis para el desarrollo de un sistema de gestión de inventario utilizando la metodología UML para el almacén "La Casa de Los Tapices" en la ciudad de Babahoyo. - Macias Manzano, Jostin Joel (2024)
The study focused on analyzing the need to develop an inventory management system using UML methodology to optimize inventory control and improve operational efficiency in the warehouse "La Casa de los Tapices" in Babahoyo. The problem detected was the manual management of inventories, which resulted in errors and lack of accuracy in the tracking of available products. To address this situation, a mixed methodology was employed that included staff interviews and customer surveys, along with document analysis. The results revealed a clear demand from staff for an automated system that would simplify daily tasks and improve inventory management. On the other hand, the surveys reflected general satisfaction among clients, although they highlighted areas for improvement, such as product availability and clarity in promotions and discounts. There was evidence of the need to implement a UML-based inventory management system to align warehouse operations with customer expectations and improve overall efficiency. It is recommended that a UML-based inventory management system be adopted to address the identified challenges and improve customer satisfaction at "La Casa de los Tapices". This approach will allow for more efficient inventory management and a more satisfying shopping experience for customers.